The role of the teacher as an organic intellectual in the light of Gramsci - Morais, Rogério de; Melo Júnior, Arlindo Lins de; Domingues, Tiago Cesar (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
The teacher's role as an organic intellectual takes place on a battlefield, which is the school itself. This dispute refers to the production of a conception of the world that is coherent, articulated and organic according to the popular will, starting from the pedagogical relations between all the individuals that constitute the living educational work. We aim to understand the role of the teacher as an organic intellectual linked to the school involved in the context of social, political and economic issues. The concept of organic intellectual for the philosophy of Antônio Gramsci is developed, relating to the role of the teacher in capitalist society. In this text, the scientific essay is used as a methodological strategy. In addition, it is understood that when there is a unity between theory and practice in the teacher's work, praxis, the same will exercise the function of organic intellectual linked to the material and immaterial needs of the social group in which the teacher can succeed in its scientific-philosophical, educational-cultural and ethical-political engagement.